2012
DOI: 10.1111/j.1365-294x.2012.05617.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular ecology and adaptation of visual photopigments in craniates

Abstract: In craniates, opsin-based photopigments expressed in the eye encode molecular 'light sensors' that constitute the initial protein in photoreception and the activation of the phototransduction cascade. Since the cloning and sequencing of the first vertebrate opsin gene (bovine rod opsin) nearly 30 years ago (Ovchinnikov Yu 1982, FEBS Letters, 148, 179-191; Hargrave et al. 1983, Biophysics of Structure & Mechanism, 9, 235-244; Nathans & Hogness 1983, Cell, 34, 807-814), it is now well established that variatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
203
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 176 publications
(224 citation statements)
references
References 329 publications
(457 reference statements)
10
203
0
8
Order By: Relevance
“…MSP and in vitro regeneration), this study has demonstrated that five opsin genes encoding a rod and four cone visual pigments are expressed in the retina of P. elegans adelaidae. These opsin genes are orthologous to the pigments classes found in other birds and the vertebrates in general (Yokoyama, 2000a;Davies et al, 2012). Although visual pigments present in many avian species have been identified, only in three species [the chicken (Okano et al, 1992), the pigeon (Kawamura et al, 1999) and the zebra finch (Taeniopygia guttata) (Yokoyama et al, 2000)] have the full complement of rod and cone opsin genes been identified and sequenced.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…MSP and in vitro regeneration), this study has demonstrated that five opsin genes encoding a rod and four cone visual pigments are expressed in the retina of P. elegans adelaidae. These opsin genes are orthologous to the pigments classes found in other birds and the vertebrates in general (Yokoyama, 2000a;Davies et al, 2012). Although visual pigments present in many avian species have been identified, only in three species [the chicken (Okano et al, 1992), the pigeon (Kawamura et al, 1999) and the zebra finch (Taeniopygia guttata) (Yokoyama et al, 2000)] have the full complement of rod and cone opsin genes been identified and sequenced.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the presence of S164/H181/Y261/T269/A292 (SHYTA) typically yields a pigment with a λ max value at 560 nm (Yokoyama, 2000a;Davies et al, 2012). Despite the presence of SHYTA in P. elegans, the λ max value determined by MSP was long-wavelength shifted at 567 nm (Fig.…”
Section: Spectral Tuning P Elegans Visual Pigmentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Electrophysiological, molecular and genetic techniques have greatly increased our knowledge of the retinal basis for vision in mammals [1][2][3][4]. Cone photoreceptorsresponsible for high acuity, colour vision in bright light-typically possess one of four spectral classes of photopigment called opsins.…”
Section: Introductionmentioning
confidence: 99%